In Vitro Antiglycation Activity of Arbutin - Jedsadayanmata, Arom (Asian Health, Science and Technology Reports, 2005)
Non-enzymatic glycosylation (glycation) between reducing sugar and protein results in formation of advanced glycation endproducts (AGEs), which is believed to play important roles in pathogenesis of diabetic and aging complications. Thus, agents that inhibit the formation of AGEs are purported to have therapeutic potentials in patients with diabetes or age-related diseases. The present study was conducted to determine glycation inhibitory activity of arbutin, a naturally occurring compound with an antioxidative property, by using an in vitro glucose-bovine serum albumin (BSA) assay. Glucose and BSA were coincubated at 60oC in the presence or absence of arbutin or aminoguanidine, a known inhibitor of glycation reaction. Following a 24-hour incubation period, the glycated BSA product was precipitated with trichloroacetic acid (TCA) and redissolved in alkaline phosphate buffered saline (PBS). The formation of glycated BSA was relatively quantitated by measuring fluorescence intensity. Excitation and emission wavelength were at 370 nm and 440 nm, respectively. The result of this study demonstrated that arbutin inhibited glycation of BSA by glucose in a dose-dependent manner. In this assay, the 50% inhibition was observed at 5 and <1 mM concentration of arbutin and aminoguanidine, respectively. Its inhibitory activity was further confirmed when the glycation reaction was allowed to proceed at lower temperature (37oC) for 14 days with similar findings. Taken together, these data indicated that arbutin possessed an in vitro antiglycation activity; however, its activity was relatively less than that of aminoguanidine when tested by glucose-BSA assay under the condition used in this study.